2017
DOI: 10.1021/acs.jpcc.7b11369
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Correlation of Electronic Structure and Carrier Dynamics in CuInS2 Nanoparticles

Abstract: In this work, we report the direct correlation of photoinduced carrier dynamics and electronic structure of CuInS2 (CIS) nanoparticles (NPs) using the combination of multiple spectroscopic techniques including steadystate X-ray absorption spectroscopy (XAS), optical transient absorption (OTA), and X-ray transient (XTA) absorption spectroscopy. XAS results show that CIS NPs contain a large amount of surface Cu atoms with ≪fourcoordination, which is more severe in CIS NPs with shorter nucleation times, indicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 41 publications
2
26
2
Order By: Relevance
“…From this, we attempt to correlate the observed quenching/brightening of the characteristic PL feature of CIS NCs under oxidizing and reducing conditions to the presence of Cu 2+ cations (“dark”) and Cu + cations (“bright”). Our simulations show that the so-called “white line”, which is the main peak observed in the Cu K-edge XANES spectrum, decreases when a small cluster is simulated compared to the bulk CIS spectrum (Figure a), in line with a decrease of the ratio between internal and surface Cu atoms . Interestingly, when additional positive charge is added to the simulated cluster, the “white line” increases more drastically (Figure a).…”
Section: Results and Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…From this, we attempt to correlate the observed quenching/brightening of the characteristic PL feature of CIS NCs under oxidizing and reducing conditions to the presence of Cu 2+ cations (“dark”) and Cu + cations (“bright”). Our simulations show that the so-called “white line”, which is the main peak observed in the Cu K-edge XANES spectrum, decreases when a small cluster is simulated compared to the bulk CIS spectrum (Figure a), in line with a decrease of the ratio between internal and surface Cu atoms . Interestingly, when additional positive charge is added to the simulated cluster, the “white line” increases more drastically (Figure a).…”
Section: Results and Discussionmentioning
confidence: 56%
“…Our in situ PL spectroelectrochemistry experiments can be very well explained by oxidation of Cu + into Cu 2+ , which results in “dark” NCs, as was suggested in Figure 1 c. To verify that electrochemical oxidation of CIS NCs indeed results in an increase in Cu 2+ cations, we measured the Cu K-edge X-ray absorption near-edge spectroscopy (XANES) spectra upon application of a reducing and oxidizing potential by in situ X-ray absorption measurements 41 44 and analyzed the observed features in the XANES pattern by simulating the spectra with standard FEFF and FDMES programs (Figures 4 and S11–13 ). From this, we attempt to correlate the observed quenching/brightening of the characteristic PL feature of CIS NCs under oxidizing and reducing conditions to the presence of Cu 2+ cations (“dark”) and Cu + cations (“bright”).…”
Section: Results and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…109 This study also showed the presence of a significant fraction of undercoordinated Cu + (i.e., coordination number <4), which were attributed to surface Cu + sites, because their concentration increased with decreasing NC size. 109…”
mentioning
confidence: 54%
“…48 We note that this assignment is consistent with the conclusions derived from the XANES measurements under laser excitation carried out by Ludwig et al on similarly sized CuInS 2 NCs. 109 A weak photoinduced absorption feature was later observed in copper-doped Cu + :CdSe NCs and interpreted similarly. 47 These observations support the mechanism proposed by Knowles et al 54 in which Cu 2+ is created only after localization of a photogenerated valence band hole (eq 2).…”
mentioning
confidence: 63%